High-risk factors for postoperative complications in patients with pancreatic disease: a single-center experience - Zhang, Man; Li, Ning; Tian, Wenjie; Xiao, Qigui; Wei, Kongyuan; Wang, Zheng; Lu, Huapeng (Frontiers in Surgery, 2025)
ObjectiveTo collect and analyse the hospital complication status of hospitalised patients with pancreatic disease in a tertiary hospital in western China and to explore the influencing factors, providing a foundation for further research.MethodsA retrospective study design was adopted. Electronic medical records of pancreatic surgery patients hospitalised at the First Affiliated Hospital of Xi'an JiaoTong University from March 1, 2024, to July 31, 2024, were retrospectively reviewed. Data on demographic characteristics, NRS2002 scores, diagnoses, laboratory results, surgical methods, and complications were collected. SPSS software was used for univariate and multivariate analyses.ResultsIn total, 172 patients, with a mean age of 60.21 ± 10.94 years, were included. Hospital complications occurred in 21.51% of pancreatic disease patients. The three most common complications were infection (14.53%), pancreatic fistula (7.56%), and cholangitis (3.49%). Univariate analysis revealed that disease diagnosis category (χ² = 8.342, P = 0.015), postoperative red blood cell (RBC) count (t = −2.552, P = 0.012), and postoperative haemoglobin concentration (Hb, g/L) (t = −2.393, P = 0.018) were risk factors for complications. Multivariate analysis confirmed that a high NRS2002 score was an independent risk factor (OR = 4.20; 95% CI: 1.017–17.368; P = 0.047).ConclusionThe hospital complication rate in pancreatic disease patients was 21.51%, with infection, pancreatic fistula, and cholangitis being the most common complications. Low postoperative RBC counts, low postoperative Hb concentrations, and high preoperative NRS2002 scores were significant risk factors. These findings underscore the potential clinical importance of integrated perioperative nutritional support and anaemia management in improving surgical outcomes for pancreatic tumour patients, warranting further investigations in larger prospective studies.